1993
DOI: 10.1007/bf01296079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of islet hormones on secretin-stimulated exocrine secretion in isolated perfused rat pancreas

Abstract: To clarify the effect of islet hormones on pancreatic ductular cell function, we measured the exocrine secretion elicited by 10 pM secretin in the presence or absence of islet hormones using an isolated perfused rat pancreas model. Insulin significantly increased secretin-stimulated pancreatic juice secretion, but not protein secretion. The potentiating effect of insulin on pancreatic juice secretion was concentration-dependent, and the maximal effect was observed with 1 microM insulin. Ouabain, a specific Na+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Although earlier studies of amino acid transport in pancreatic fragments and acini failed to demonstrate a regulatory role for insulin (Bieger, Weicker & Haymovits, 1979;Korc, Iwamoto, Sankaran, Williams & Goldfine, 1981), glucose and neutral amino acid transport, protein synthesis and exocrine secretion are stimulated by insulin (see Williams & Goldfine, 1985;Norman & Mann, 1987). Endogenous insulin, released in response to a vascular glucose challenge, potentiates cholecystokinin (CCK)-induced pancreatic secretion (Saito et al 1980), and exogenous insulin has been shown to increase secretin-stimulated pancreatic juice secretion (Hasegawa, Okabayashi, Koide, Kido, Okutani, Matsushita, Otsuki & Kasuga, 1993). Moreover, concentrations of insulin antiserum, known to abolish postprandial increases in plasma insulin, have been found to inhibit CCK-and secretin-mediated pancreatic secretion (Lee, Zhou, Ren, Chang & Chey, 1990;Lee, Lee, Kim, Chang & Chey, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies of amino acid transport in pancreatic fragments and acini failed to demonstrate a regulatory role for insulin (Bieger, Weicker & Haymovits, 1979;Korc, Iwamoto, Sankaran, Williams & Goldfine, 1981), glucose and neutral amino acid transport, protein synthesis and exocrine secretion are stimulated by insulin (see Williams & Goldfine, 1985;Norman & Mann, 1987). Endogenous insulin, released in response to a vascular glucose challenge, potentiates cholecystokinin (CCK)-induced pancreatic secretion (Saito et al 1980), and exogenous insulin has been shown to increase secretin-stimulated pancreatic juice secretion (Hasegawa, Okabayashi, Koide, Kido, Okutani, Matsushita, Otsuki & Kasuga, 1993). Moreover, concentrations of insulin antiserum, known to abolish postprandial increases in plasma insulin, have been found to inhibit CCK-and secretin-mediated pancreatic secretion (Lee, Zhou, Ren, Chang & Chey, 1990;Lee, Lee, Kim, Chang & Chey, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin has a direct stimulatory action on fluid secretion. In isolated perfused rat pancreas, insulin significantly increases secretin-stim-Bertelli, Bendayan ulated pancreatic juice secretion, but not protein secretion (Hasegawa et al 1993). Anti-insulin antibodies, on the other hand, reduce spontaneous fluid secretion and suppress the increase evoked by a meal or by secretin/CCK infusion (Lee et al 1990).…”
Section: Islet Influence On Pancreatic Duct Secretionmentioning
confidence: 99%
“…However, the real physiological importance of this action is far from being established (Chey 1993). In isolated rat pancreas, glucagon significantly inhibits secretin-stimulated pancreatic juice secretion (Hasegawa et al 1993). In conscious rats, glucagon reduces caerulein-evoked pancreatic secretion in terms of the volume of pancreatic juice, bicarbonate, and protein output (Biedzinski et al 1987).…”
Section: Islet Influence On Pancreatic Duct Secretionmentioning
confidence: 99%
See 2 more Smart Citations